The Stability of Buddhism and Persistence of a Sufficient Living of the Laotians make Self-Immunity to Changing Socio-cultural in the Urbanity of Vientiane, Lao PDR - Phukamchanoad, Phusit (Journal of Ecohumanism, 2024)
The research studied self-sufficiency living through the frugality practice of Laotians living in Vientiane city area. Data collections were performed using 400 surveys and 30 sets of questionnaires with community leaders, young adults, state officers, private staffs, general citizens and youths. Result found that Vientiane Laotians are strictly Buddhism and they have more than two occupations due to low wages and high cost of livings. The majority of the citizens are part of young adults’ group and women group. Due to high cost of living, urban living required Laos people to be frugal on a daily basis. They dine together and works are self-reliance. Sustainability and sufficiency are practiced among households at a medium level, but people portrayed extremely high generosity level towards each other. Environment and nature conservation are a big part of their ‘normality’. Vientiane Laotians often attend social gatherings after work. Their demonstrated strong beliefs in Buddhism, of which the religion has encouraged them to live in unity following the Sufficiency Economy Dharmachakra Model.